Japanese and North American Alzheimer's Disease Neuroimaging Initiative studies: Harmonization for international trials. Issue 8 (9th May 2018) - Iwatsubo, Takeshi; Iwata, Atsushi; Suzuki, Kazushi; Ihara, Ryoko; Arai, Hiroyuki; Ishii, Kenji; Senda, Michio; Ito, Kengo; Ikeuchi, Takeshi; Kuwano, Ryozo; Matsuda, Hiroshi; ,; et al.
Abstract: Introduction: We conducted Japanese Alzheimer's Disease Neuroimaging Initiative (J‐ADNI) and compared the basic characteristics and progression profiles with those of ADNI in North America. Methods: A total of 537 Japanese subjects with normal cognition, late amnestic mild cognitive impairment (LMCI), or mild Alzheimer's disease (AD) were enrolled using the same criteria as ADNI. Rates of changes in representative cognitive or functional measures were compared for amyloid positron emission tomography‐ or cerebrospinal fluid amyloid β(1–42)‐positive LMCI and mild AD between J‐ADNI and ADNI. Results: Amyloid positivity rates were significantly higher in normal cognition of ADNI but at similar levels in LMCI and mild AD between J‐ADNI and ADNI. Profiles of decline in cognitive or functional measures in amyloid‐positive LMCI in J‐ADNI (n = 75) and ADNI (n = 269) were remarkably similar, whereas those in mild AD were milder in J‐ADNI (n = 73) compared with ADNI (n = 230). Discussion: These results support the feasibility of bridging of clinical trials in the prodromal stage of AD between Asia and western countries.